Cardioembolic stroke: everything has changed. Issue 2 (9th March 2018) - Spence, J David
Abstract : Historically, because of the difficulty of using warfarin safely and effectively, many patients with cardioembolic stroke who should have been anticoagulated were instead given ineffective antiplatelet therapy (or no antithrombotic therapy). With the arrival of new oral anticoagulants that are not significantly more likely than aspirin to cause severe haemorrhage, everything has changed. Because antiplatelet agents are much less effective in preventing cardioembolic stroke, it is now more prudent to anticoagulate patients in whom cardioembolic stroke is strongly suspected. Recent advances include the recognition that intermittent atrial fibrillation is better detected with more prolonged monitoring of the cardiac rhythm, and that percutaneous closure of patent foramen ovale (PFO) may reduce the risk of stroke. However, because in most patients with stroke and PFO the PFO is incidental, this should be reserved for patients in whom paradoxical embolism is likely. A high shunt grade on transcranial Doppler saline studies, and clinical clues to paradoxical embolism, can help in appropriate selection of patients for percutaneous closure. For patients with atrial fibrillation who cannot be anticoagulated, ablation of the left atrial appendage is an emerging option. It is also increasingly recognised that high levels of homocysteine, often due to undiagnosed metabolic deficiency of vitamin B12, markedly increase the risk of stroke in atrial fibrillation, and that B vitamins (folic acid and B12 ) do prevent stroke by lowering homocysteine. However, with regard to B12, methylcobalamin should probably be used instead of cyanocobalamin. Many important considerations for judicious application of therapies to prevent cardioembolic stroke are discussed.